A system-independent 3D coordinate–based planning method for hexapod deformity correction: a synthetic bone model study and preliminary clinical experience - Nath Adulkasem; Bavornrit Chuckpaiwong; Direk Tantigate; Chatupon Chotigavanichaya; Perajit Eamsobhana; Thanase Ariyawatkul; Jidapa Wongcharoenwatana; Pongpak Bhumiwat (Scientific Reports, 2026)
Abstract Computer-assisted hexapod external fixators rely on system-specific planning software that is closely linked to the hardware configuration. This may limit flexibility in construct design and cross-system application. A three-dimensional (3D) coordinate–based planning method was developed to allow deformity correction independent of system-specific software and hardware parameters. An experimental study was conducted using tibial bone models instrumented with three different hexapod external fixator systems: the Taylor Spatial Frame, the Ortho-SUV system, and a modified Ilizarov hexapod construct. A total of 12 deformity scenarios were created, including angulation and translation in multiple planes. Deformity correction was planned using a developed 3D coordinate–based method, in which key bone and frame landmarks were obtained as 3D coordinates from postoperative computed tomography and used to calculate the required strut adjustments. Residual deformity was assessed using mean absolute error in each plane. The results were compared with conventional two-dimensional system-specific planning software. A preliminary clinical application was also reported. The 3D coordinate–based method demonstrated high correction accuracy, with residual deformities of 0.9° ± 0.5° in the coronal plane, 4.7° ± 2.1° in the sagittal plane, and 0.5° ± 0.9° in axial rotation. Translational errors were 2.8 ± 2.4 mm mediolaterally, 3.4 ± 2.8 mm anteroposteriorly, and 1.4 ± 1.6 mm in length. Performance was similar across the three hexapod systems. Strut length changes from baseline were modest and comparable among systems. When compared with conventional planning software, the 3D coordinate-based method showed similar correction accuracy across all six degrees of freedom, with a trend toward smaller residual deformity. The preliminary clinical application demonstrated satisfactory correction across all planes. The 3D coordinate–based planning method achieved accurate correction of complex three-dimensional deformities across multiple hexapod systems. Correction performance was comparable to established system-specific planning methods, while allowing greater flexibility in construct design and cross-system application. Although the findings are based primarily on in vitro experiments with a preliminary clinical application, the results support the feasibility of the proposed method. Further prospective clinical studies are required to confirm its effectiveness.